Exploring the concept of need in people with very severe chronic obstructive pulmonary disease: a qualitative study. Issue 4 (26th August 2015) - Kendall, Marilyn; Buckingham, Susan; Ferguson, Susie; MacNee, William; Sheikh, Aziz; White, Patrick; Worth, Allison; Boyd, Kirsty; Murray, Scott A; Pinnock, Hilary
Abstract : Background: Despite apparent unmet needs, people with chronic obstructive pulmonary disease (COPD) rarely ask for help. We explored the concept of need from the perspective of patients, their family carers and professionals. Methods: We recruited inpatients at two National Health Service (NHS) Lothian hospitals to a structured, holistic review of care needs delivered at home by a respiratory nurse 4 weeks postdischarge. Using semistructured interviews and group discussions, review notes and field-notes we explored the views of patients, carers and professionals on perceptions of need and the actions requested. Data were analysed thematically using Bradshaw's classification of need. Results: 14 patients, 3 carers, 28 professionals provided 36 interviews and 2 discussion groups. Few needs were identified by our intervention and few actions planned. Professionals identified 'normative' needs some of which had been addressed during routine discharge planning. Other needs (physical/psychological limitations, social/financial concerns, existential issues) were 'felt' by patients and carers but articulated in response to the researcher's questions rather than actively 'expressed'. Patients often did not wish any action to address the problems, preferring care from family members rather than formal agencies. Many spoke of the over-arching importance of retaining a sense of independence and autonomy, considering themselves as ageing rather than ill. Conclusions: In contrast to professionally-defined 'normative' needs, patients rarely perceived themselves as needy, accepting their 'felt' needs as the result of a disability to which they had now adapted. Sensitive approaches that foster independence may enable patients to 'express' needs that are amenable to help without disturbing the adaptive equilibrium they have achieved. Trial registration number: NCT01650480.